Radiographic evaluation of the lumbar lordotic angle of the spine in a population of Nigerians - Oyakhire, Michael O; Didia, Blessing C; Yellow, Bob Evans (Asian Journal of Medical Sciences, 2013)
Objectives: For Nigerian Africans, quantitative reference values of osteometric parameters of the human spine are scarce. This study was therefore carried out to metrically evaluate and document the characteristics of the Lumbar lordotic angle, in a population of Nigerians. Materials & Method: Using the Cobb 4-line method, we studied 300 lateral radiographs selected from three tertiary health facilities. There were 156 females (52%) and 144 males (48%) with age range between 18 and 76years. Results were analyzed statistically with the computer based SPSS Version 17, Chicago IL. Taking a confidence level of 0.05 as indicative of statistical significance, the student’s t –test was used to estimate differences between means, and a probability density function curve ,to evaluate the distribution pattern of the angle of lumbar lordosis. Results: Mean (± SD) of the Lumbar lordotic angle was 48.450 ± (9.280). A statistically significant association was found between Lumbar lordotic angle and age (P<0.05). Females had significantly higher Lumbar lordotic angles compared with males (P<0.05). Variations were also observed between the lumbar lordotic angles of Nigerians and those of Caucasians. These results will be useful in many areas of medical practice, and research. DOI: http://dx.doi.org/10.3126/ajms.v4i3.4300 Asian Journal of Medical Sciences 4(2013) 69-75